A revision of the Egyptian species of the genus Actorthia Kröber (Diptera: Therevidae: Phycinae) - Badrawy, Haitham B. M.; Mohammad, Salwa K. (Zootaxa, 2013)
The genus Actorthia Kröber, 1912 was described based on a single female from Tourrah (Egypt) and is revised for the first time since the original description. Actorthia khedivialis (Becker, 1912) is newly synonymized with A. frontata (Kröber, 1912) based on examination of the type specimens of both species recently discovered in the Cairo University Collection (Egypt) and Natural History Museum (Austria), respectively. Actorthia efflatouni Kröber, 1925 is confirmed as a synonym of A. micans (Kröber, 1923) and Actorthia olivierii (Macquart, 1840) is transferred to Phycus. Actorthia pulchella Kröber, 1927 is recorded in Israel for the first time. The three Egyptian species of Actorthia are diagnosed and illustrated along with colour images of the type specimens, and a key to the Egyptian species is included.